2017
DOI: 10.1371/journal.pbio.2001132
|View full text |Cite
|
Sign up to set email alerts
|

A Webcast of Bird Nesting as a State-of-the-Art Citizen Science

Abstract: The quality of people’s knowledge of nature has always had a significant influence on their approach to wildlife and nature conservation. However, direct interactions of people with nature are greatly limited nowadays, especially because of urbanization and modern lifestyles. As a result, our isolation from the natural world has been growing. Here, we present an example of a state-of-the-art Citizen Science project with its educational, scientific, and popularizing benefits. We conclude that modern media and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Zárybnická et al . () found statistically significant knowledge gains by students about birds, and other studies outside of this review reported that NBCS messages were often conveyed to local communities through presentations and media coverage (Eastman et al . ).…”
Section: Can We Preach Beyond the Choir?supporting
confidence: 53%
See 2 more Smart Citations
“…Zárybnická et al . () found statistically significant knowledge gains by students about birds, and other studies outside of this review reported that NBCS messages were often conveyed to local communities through presentations and media coverage (Eastman et al . ).…”
Section: Can We Preach Beyond the Choir?supporting
confidence: 53%
“…However, the extent to which NBCS can influence connections with nature among the young has yet to be explored fully. Zárybnická et al (2017) found statistically significant knowledge gains by students about birds, and other studies outside of this review reported that NBCS messages were often conveyed to local communities through presentations and media coverage (Eastman et al 2014). The major advantage of working in schools is that participant selection bias is reduced or even removed, as experiences in nature are offered to diverse communities.…”
Section: Can We Preach Beyond the Choir?mentioning
confidence: 57%
See 1 more Smart Citation
“…These school activities varied with student ages and included creating pictures, stories, handcrafts, and video clips, as well as the extraction of biological information from video recordings and its presentation in classrooms (for details, see Zárybnická et al. ). Students in more advanced grades at vocational training schools have developed their technical skills in material, machining, and producing documentation in the course of making wooden boxes used for our SNBox system.…”
Section: Discussionmentioning
confidence: 99%
“…The most basic application is the dissemination of live streaming and video capturing of bird activities in their nests via social media (Zárybnická et al. ). Availability of such video creates the potential for educational activities such as direct observation of animal life on screens placed in schools that can supplement generic textbook information with real‐life bird observation.…”
Section: Introductionmentioning
confidence: 99%